2017
DOI: 10.1080/14606925.2017.1352833
|View full text |Cite
|
Sign up to set email alerts
|

Libraries of Things as a new form of sharing. Pushing the Sharing Economy

Abstract: Abstract:Although the willingness to share is huge, sharing is rarely applied in everyday life, because many current Sharing Economy offers are not practicable. This paper asks what contributions an innovative Sharing Service -a library not simply lending books but a wider range of items -can make to close the gap between willingness to share and practice. Most of these innovative libraries were founded in the last few years, but many still fail to overcome the identified gap. As global environmental problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…This is despite public libraries being commonly proposed as potential centres for sustainable community development [37]. Studies on consumer response to such libraries indicate that there is a high willingness to share rather than own across many countries, but despite this, sharing is rarely put into practice, in part due to a lack of structured sharing options [38]. A study of LoTs in Germany found that users are motivated by cost savings, convenience and positive social aspects of sharing, while barriers include lack of awareness about LoTs, hygiene issues, security, low quality of items, high effort and unwanted dependency on other people [38].…”
Section: Libraries Of Things (Lots)mentioning
confidence: 99%
See 3 more Smart Citations
“…This is despite public libraries being commonly proposed as potential centres for sustainable community development [37]. Studies on consumer response to such libraries indicate that there is a high willingness to share rather than own across many countries, but despite this, sharing is rarely put into practice, in part due to a lack of structured sharing options [38]. A study of LoTs in Germany found that users are motivated by cost savings, convenience and positive social aspects of sharing, while barriers include lack of awareness about LoTs, hygiene issues, security, low quality of items, high effort and unwanted dependency on other people [38].…”
Section: Libraries Of Things (Lots)mentioning
confidence: 99%
“…Studies on consumer response to such libraries indicate that there is a high willingness to share rather than own across many countries, but despite this, sharing is rarely put into practice, in part due to a lack of structured sharing options [38]. A study of LoTs in Germany found that users are motivated by cost savings, convenience and positive social aspects of sharing, while barriers include lack of awareness about LoTs, hygiene issues, security, low quality of items, high effort and unwanted dependency on other people [38]. Additionally, there were discrepancies with respect to supply and demand of loanable goods as users are not keen to lend personal possessions to strangers and completely let go of them, unless they are of low quality.…”
Section: Libraries Of Things (Lots)mentioning
confidence: 99%
See 2 more Smart Citations
“…4 Research has shown that there is an interest in a "Library of Things" and that patrons want access to items and workshops for their use. 5 As a large public university, UF has an enrollment of around 55,000 students, of which some 10,000 are associated with the 9 departments, 15 degree programs, and 20 centers and institutes within the Herbert Wertheim College of Engineering. About two-thirds of the engineering students are undergraduates and all are required to have a laptop computer.…”
Section: Background/literature Reviewmentioning
confidence: 99%